Role of Linseed oil in preventing peri-ileostomy skin excoriation - Kumar Saxena, Sunil (International Journal of Medical Research and Review, 2014)
Introduction: Our gastrointestinal tract bears the entire burden to give us energy for living. Sometimes it gives way and causes lot of sufferings. Many surgeries have been devised to save the lives of patients suffering from these gastrointestinal diseases and stoma formation is one such surgery. Stoma though saves life but it itself causes lot of problems and the most dreaded one is peristomal skin excoriation. Peri-stomal excoriation can be broadly defined as any wound that is adjacent to a stoma, including erosion or ulceration of the peri-stomal skin. It is most dangerous in iliostomy patients. This study was carried out to study the effects of linseed oil in preventing peri-iliostomy skin excoriation. Materials and Methods: This study was carried out at Bundelkhand Medical College, Sagar from 2009 to 2012. 24 patients were included in this study in whom iliostomy was done due to perforation peritonitis. Linseed or flax seed oil was applied in all the patients to prevent peri-iliostomy skin excoriation. Results: In this study only 3 patients developed minor skin excoriation, rest all were having healthy peri-iliostomy skin with continued use of linseed oil till stoma closure was done. Conclusion: Linseed oil gives effective protection and helps in preventing peristomal skin excoriation rather than any other available modality. It is locally available, very economical and its indigenous use has the potential of minimizing the agony and complications associated with peri-ileostomy skin excoriation.